The Improvement of Elderly Acceptance in Cronic Pain, Comfort, and Quality of Life through Acceptance and Commitment Therapy (ACT) - Dhina Widayati; Ahmad Yusuf; Rizki Fitryasari P.K. (Universitas Airlangga, 2014)
Introduction: Chronic joint pain is a problem for the majority of elderly. Psychosocial factors have a great impact on people with chronic pain. The acceptance of pain in people with chronic pain can increase their activity daily living, comfort, and quality of life. Acceptance And Commitment Therapy (ACT) is a form of psychotherapy which effective in the management of chronic pain. The objective of this study was to analyze the effect of ACT on improvement acceptance of chronic pain, comfort, and quality of life elderly with chronic joint pain.Method: This study was used a quasy experiment pre-post test control group design. Population were elderly who lived at UPT PSLU Jombang di Pare-Kediri. Sample were 32 respondents gotten by purposive sampling, divided into experiment and control group. Independent variable was ACT, and dependent variables were pain acceptance, comfort, and quality of life elderly with chronic joint pain. Data were collected by using questionnaire with CPAQ (pain acceptance), GCQ (comfort) and WHO-QOLBREF (Quality of Life). Data then analyzed by using Wilcoxon Signed Ranks Test, Mann Whitney U Test, Paired t test and Independent Samples t test with significance value of 0.05.Result: The results had showed that there was an influence ACT to improvement acceptance of chronic pain (p=0,003), comfort (p=0,008), and quality of life elderly with chronic joint pain (p=0,002).Discussion: ACT improved pain acceptance, comfort, and quality of life of elderly with joint chronic pain. Geriatric nurses should include psychosocial activities as a routine activities, as an effort to improve the quality of life. Beside that, the quality of nursing care for elderly can be improved.